Economic and social burden due to injuries and violence in Nepal: A cross-sectional study - Joshi, SK; Shrestha, S (Kathmandu University Medical Journal, 2010)
Background: Injury and violence cause five million deaths annually in the world which is around 9% of the global mortality. Eight out of fifteen leading causes of deaths in the age group 15-25 years are injury related. Objective: The objective of this study was to assess the incidence, severity and socio-economic burden of injuries and violence in two cities of Nepal. Materials and methods: Relevant data was collected from 17th August 2008 to 16th September 2008 from injured patients attending emergency departments at six health centres in two cities. Results: In total, 505 injury cases were reported. 42.5% of the injuries occurred in roads and 34.1% at home. 65% of road traffic injuries involved motorcycles. The majority (60%) of the injured subjects were economically active. A single injury case cost 126.2 US$ including all the expenses and the loss due to inability to work. Conclusion: The high incidence of injuries, especially road traffic injuries, adds a huge economic burden to nation. Key words: disabilities; economic burden; injuries; violence DOI: 10.3126/kumj.v7i4.2752 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 344-350